Genetically Encoded Self-Assembling Protein Nanoparticles for the Targeted Delivery In Vitro and In Vivo - Anastasiia S. Obozina; Elena N. Komedchikova; Olga A. Kolesnikova; Anna M. Iureva; Vera L. Kovalenko; Fedor A. Zavalko; Tatiana V. Rozhnikova; Ekaterina D. Tereshina; Elizaveta N. Mochalova; Victoria O. Shipunova (MDPI AG, 2023)
Targeted nanoparticles of different origins are considered as new-generation diagnostic and therapeutic tools. However, there are no targeted drug formulations within the composition of nanoparticles approved by the FDA for use in the clinic, which is associated with the insufficient effectiveness of the developed candidates, the difficulties of their biotechnological production, and inadequate batch-to-batch reproducibility. Targeted protein self-assembling nanoparticles circumvent this problem since proteins are encoded in DNA and the final protein product is produced in only one possible way. We believe that the combination of the endless biomedical potential of protein carriers as nanoparticles and the standardized protein purification protocols will make significant progress in "magic bullet" creation possible, bringing modern biomedicine to a new level. In this review, we are focused on the currently existing platforms for targeted self-assembling protein nanoparticles based on transferrin, lactoferrin, casein, lumazine synthase, albumin, ferritin, and encapsulin proteins, as well as on proteins from magnetosomes and virus-like particles. The applications of these self-assembling proteins for targeted delivery in vitro and in vivo are thoroughly discussed, including bioimaging applications and different therapeutic approaches, such as chemotherapy, gene delivery, and photodynamic and photothermal therapy. A critical assessment of these protein platforms' efficacy in biomedicine is provided and possible problems associated with their further development are described.